1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Integration by substitution

  1. Dec 9, 2009 #1
    1. The problem statement, all variables and given/known data
    Compute the indefinite integral.

    ∫(x^2 + 1)^(-5/2) dx

    3. The attempt at a solution
    I have a hunch that I need to substitute x = tan(u) but, as always, my lack of trig skills are holding me back.
     
  2. jcsd
  3. Dec 9, 2009 #2

    Mark44

    Staff: Mentor

    Yes, that's the right substition.

    If x = tan u, dx = ?
     
  4. Dec 9, 2009 #3
    So dx = sec^2 u du?
     
  5. Dec 9, 2009 #4

    Mark44

    Staff: Mentor

    Right. And you also have the du, so good job. You'll need to substitute for the x^2 + 1 part, so that's tan^2(x) + 1, right?

    When you're done with you trig substitution, your new integral will be completely in terms of u and du, with x and dx completely gone.
     
  6. Dec 9, 2009 #5
    I plugged in the x = tan u and dx = sec^2 u du, and I got
    ∫[tan^2(u) + 1]^(-5/2) * sec^2(u) du
    ==> ∫[sec^2(u)]^(-5/2) * sec^2(u) du
    ==> ∫[sec^2(u)]^(-3/2) du
    after integration I end up with (-3/2)(tanu/secu)
    If I continue on and cancel out the cosines, I end up with (-3/2)sinu.
    I don't know how to get this back in terms of x.
     
  7. Dec 9, 2009 #6
    Wait, I think I got this.
    I didn't write out all of my steps in my last reply..so I'll go back one or two, to one I skipped.
    (-3/2)[tan(u) / √sec^2(u)]
    ==>(-3/2) [tanu / √(tan^2u + 1)]
    ==>-3x / 2√(x^2 + 1)
     
    Last edited: Dec 9, 2009
  8. Dec 9, 2009 #7

    Mark44

    Staff: Mentor

    Don't use ==> when you mean =.

    Also, don't forget your constant of integration. I didn't check your answer, but you can do that. If your antiderivative is correct, you should be able to differentiate it and get back the original integrand. IOW, d/dx(-3x/2sqrt(x^2 + 1)) should equal (x^2 + 1)^(-5/2).
     
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook